Towards improving livelihood of smallholder livestock farmers under communal farming - Wesley, Kutu Lesetja; Mahlengule, Zwane Elliot; Simon, Letsoalo Sebatana (Research in Agriculture Livestock and Fisheries, 2025)
This review examines the various opportunities and challenges faced by smallholder livestock farmers on communal land, highlighting the multiple roles of livestock as economic, social, cultural, and environmental assets. Despite playing a critical role in rural livelihoods, smallholder livestock farmers encounter various challenges, such as limited access to extension services, livestock theft, movement restrictions, and interference from traditional authorities. This paper draws on a literature review and combines findings from twenty-nine articles, twenty-eight reports, and eight university repository theses published between 2000 and 2024. Key findings show that livestock farming remains crucial for livelihoods, supporting food security, income generation, and socio-economic well-being. The conclusion emphasizes the importance of promoting sustainable livelihood strategies to tackle the specific challenges encountered by smallholder livestock farmers. Future research should investigate the lasting impacts of extension services and community-based natural resource management on household income, food security, and livestock productivity. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 203-217